Optimalizatiom use of Seagrass Leafs Thalassia hemprichii As Natural Antioksidan Source - Riki Tristanto; Megawati Arsita Putri; Anggun P. Situmorang; Suryanti Suryanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2014)
Seagrass is a wealth of marine resources, one of the ecosystems found in coastal areas, able to produce a variety of secondary metabolites, and one water plant that has important benefits that can replace natural source of antioxidants that seagrass (seagrass). Seagrasses are flowering plants (Angiospermae) who can adjust himself to life in the sea water. The purpose of this study was to determine the antioxidant potential in seagrass leaves. Extraction using maceration with the way the samples were stored by using the solvent n-hexane, ethyl acetate and methanol for each 1x24 hours after it evaporated with a vacuum rotary evaporimeter to obtain a crude extract, then extract tested by using antioxidant aktvitas diphenilpycrylhydrazil (DPPH). Antioxidant activity test carried out by the ability of the samples used in reducing the stable free radical diphenilpycrylhydrazil (DPPH). Three milliliters diphenilpycrylhydrazil (DPPH) as a positive control was weighed and added to methanol with a ratio of 1:3. An additional 2 mg of DPPH was diluted with 50 mL of methanol and added at each 1 mL to 3 mL of methanol at a concentration of 75 ppm, 125 ppm and 175 ppm. DPPH mixture is homogenized and rested for 30 minutes. Antioxidant activity assay on leaf Seagrass Thalassia hemprichii showed that the IC50 value of 25.98344501. This value indicates that the samples tested were able to inhibit the free radicals are very strong. Samples containing great potential in the utilization as a source of natural antioxidants  Keywords : Extraction, Maceration, Antioxidant, DPPH